HYPOGLYCEMIC EFFECT OF AQUEOUS FRUIT EXTRACT OF FICUS BENGALENSIS IN NORMAL AND STREPTOZOTOCIN INDUCED DIABETIC RATS - G. CH. D. NAGALAKSHMI; RAO, S. SRINIVASA; G. FAREEDA (The Bioscan, 2010)
The aim of the present study was to evaluate the antidiabetic and ameliorative potential of aqueous fruit extract of Ficus bengalensis (FB) in streptozotocin (STZ) induced diabetic rats. The effect of oral administration of aqueous fruit extract of FB on blood glucose, change in body weight, carbohydrate metabolizing enzymes, total cholesterol and lipid peroxidation in liver of STZ -induced diabetic rats were studied. Treatment of aqueous fruit extract reduced the rise in blood glucose levels and improved the enzyme acitivities to near normal in diabetic rats.